The use of prehospital blood products in the resuscitation of trauma patients: a review of prehospital transfusion practices and a description of our regional whole blood program in San Antonio, TX. (1st August 2019) - Pokorny, Douglas M.; Braverman, Maxwell A.; Edmundson, Philip M.; Bittenbinder, David M.; Zhu, Caroline S.; Winckler, Christopher J.; Schaefer, Randall; McGinity, Ashley C.; Epley, Eric; Eastridge, Brian J.; Nicholson, Susannah E.; Stewart, Ronald M.; et al.
Abstract : Background: Prehospital management of the traumatically injured patient has evolved significantly since the organization of emergency medical services across the United States in the 1970s. Initially focusing on the utilization of crystalloid solutions to restore shed blood volume, robust military and civilian trauma experiences led to a modern day shift towards balanced blood component and ultimately whole blood use for immediate volume replacement. In addition, prehospital transfusion or remote damage control resuscitation (RDRC) has been widely adopted. This has led to point of injury resuscitation using blood products both in the United States and abroad. Objectives: This article will review the evolution of civilian and military prehospital resuscitation as well as the current practice of prehospital whole blood transfusion in the civilian trauma population in the United States. Additionally, we will provide an overview of our regional trauma system's use of whole blood with focus on the programme infrastructure, donor programme, product rotation schedule and logistical challenges. Finally, we provide three case report examples of the effective use of whole blood in our civilian emergency medical services (EMS) programs.